AKTIVITAS ANTIBAKTERI EKSTRAK BAWANG PUTIH (Allium sativum) DAN BLACK GARLIC TERHADAP Escherichia coli SENSITIF DAN MULTIRESISTEN ANTIBIOTIK - Putri, Desfika Ardia; Rahayu, Triastuti (Universitas Sebelas Maret, 2014)
Abstract- The purpose of this research was to determine the antibacterial activity of garlic extract and black garlic against E.coli sensitive and resistant to antibiotics. This research is an experiment with 2 factors : 1) the type of extract (garlic and garlic Black), 2) test bacterial strain (E. coli sensitive and resistant to antibiotics). Solvent extraction using 20% ethanol, 1: 1 and then centrifuged. Antibacterial activity test by well diffusion method. Parameter study is inhibition zone formed around the wells. The results showed that extracts of garlic has antibacterial activity against E.coli sensitive (14.22 mm) and antibiotic-resistant E.coli (22.2 mm), while the black garlic extract showed no antibacterial activity.Â Keywords: garlic, black garlic, E.coli